Digital Talking Book Player for the Visually Impaired Using FPGAs - Nazemi, A.; Ortega-Sanchez, Cesar; Murray, Iain (IEEE Computer Society, 2011)
The Digital Talking Book (DTB) player is a device for the visually impaired to read, search, navigate and bookmark written material using DAISY and EPUB standards. This paper presents the design and implementation of a DTB player in an FPGA-based embedded system to play audio books containing MP3 (Daisy) files and utilize Text to Speech Synthesis (TTS) for text only books or EPUB books.